Piperonylic acid alters growth, mineral content accumulation and reactive oxygen species-scavenging capacity in chia seedlings. Issue 3 (26th May 2022) - Nkomo, Mbukeni; Gokul, Arun; Ndimba, Roya; Badiwe, Mihlali; Keyster, Marshall; Klein, Ashwil
Abstract: p -Coumaric acid synthesis in plants involves the conversion of phenylalanine to trans -cinnamic acid via phenylalanine ammonia-lyase (PAL), which is then hydroxylated at the para-position under the action of trans -cinnamic acid 4-hydroxylase. Alternatively, some PAL enzymes accept tyrosine as an alternative substrate and convert tyrosine directly to p- coumaric acid without the intermediary of trans -cinnamic acid. In recent years, the contrasting roles of p- coumaric acid in regulating the growth and development of plants have been well-documented. To understand the contribution of trans -cinnamic acid 4-hydroxylase activity in p -coumaric acid-mediated plant growth, mineral content accumulation and the regulation of reactive oxygen species (ROS), we investigated the effect of piperonylic acid (a trans -cinnamic acid 4-hydroxylase inhibitor) on plant growth, essential macroelements, osmolyte content, ROS-induced oxidative damage, antioxidant enzyme activities and phytohormone levels in chia seedlings. Piperonylic acid restricted chia seedling growth by reducing shoot length, fresh weight, leaf area measurements and p -coumaric acid content. Apart from sodium, piperonylic acid significantly reduced the accumulation of other essential macroelements (such as K, P, Ca and Mg) relative to the untreated control. Enhanced proline, superoxide, hydrogen peroxide and malondialdehyde contents were observed. The inhibition of trans -cinnamic acid 4-hydroxylase activity significantly increased the enzymatic activities of ROS-scavenging enzymes such as superoxide dismutase, ascorbate peroxidase, catalase and guaiacol peroxidase. In addition, piperonylic acid caused a reduction in indole-3-acetic acid and salicylic acid content. In conclusion, the reduction in chia seedling growth in response to piperonylic acid may be attributed to a reduction in p -coumaric acid content coupled with elevated ROS-induced oxidative damage, and restricted mineral and phytohormone (indole-3-acetic acid and salicylic) levels. Abstract : In this study we investigated the impact of a potent irreversible inhibitor (piperonylic acid) of coumarate-4-hydroxylase, on the physio-biochemical responses of chia seedlings. The results showed that piperonylic acid induced oxidative damage which resulted in restricted plant growth. Piperonylic acid also augmented proline content and activated ROS-scavenging antioxidant enzyme activities which was not sufficient to reduce the ROS-induced damage. In addition, we also observed a reduction in p -coumaric acid content, macronutrient accumulation and phytohormone levels which support the hypothesis that p -coumaric acid is an important signalling molecule for chia seedling growth.